Bon Cabai Sebagai Alternatif Produk Olahan Cabai dan Peningkatan Pendapatan Petani di Saat Pandemi Covid-19 - Heri Akhmadi; Pujastuti Sulistyaning Dyah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Chili is a widely cultivated plant by farmers in the Ngentak sub-village, Seloharjo Village, Pundong District, Bantul Regency, Special Region of Yogyakarta. In general, chili is sold as a fresh product or utilized for daily consumption. However, chili price fluctuation, especially during the harvest season and exacerbated by the Covid-19 pandemic, sometimes causes farmers to experience losses since there is a limited alternative of chili processed products. This community service aims to find an alternative of chili processed products to increase the added value of chili and as an alternative to increasing farmers' income during a pandemic. The methods used are survey, observation, and training. The result of this community service program is the development of processed chili products in the form of chili powder which can be an alternative to processed chili-based products when the chili price falls. This activity involves the Women Farmers Group as well as enlivens the group activities. Besides being an alternative to processed chili products, the development of this chili powder product can also be part of an effort to increase farmers' income, especially during a pandemic.